Replacement of the name Pristimantis viridis Valencia, Yánez-Muñoz, Betancourt-Yépez, Terán-Valdez y Guayasamin, 2010 - Jorge H. Valencia; Mario H. Yánez-Muñoz; Raquel Betancourt-Yépez; Andrea Terán-Valdez; Juan M. Guayasamin (ACI Avances en Ciencias e Ingenierías, 2011)
Recently, Valencia et al. [1] we described a new species of Pristimantis from the northwestern foothills of Ecuador. However, we made a mistake in using a specific epithet previously occupied for a frog of eastern and western foothills of Antioquia, Colombia [2]. Under Chapter 12, Article 53.3 of the International Code of Zoological Nomenclature ICZN, Pristimantis viridis Valencia, Yánez-Muñoz, Betancourt-Yépez, Terán-Valdezy Guayasamin, 2010 is considered a junior homonym. To solve this problem, and following the provisions of Art. 60.3 of ICZN [3], we propose the name Pristimantis rufoviridis nomen novum replacing Pristimantis viridis Valencia, Yánez-Muñoz, Betancourt-Yépez, Terán-Valdez y Guayasamin. The specific epithet rufoviridis comes from the combination of words in Latin rufus (red, reddish) and viridis (green), and refers to the greenish color with red spots on the back of this frog. The rufoviridis epithet is used as a noun in apposition. Although the color pattern is green in the two species, P viridis has a pale green or “apple green” immaculate without obvious stains [2], as opposed to P rufoviridis which has obvious reddish spots. As P rufoviridis, P viridis has no clear phylogenetic position within the genre Pristimantis [2].